Incidence, Outcomes, and Risk Factors of Community-Acquired and Hospital-Acquired Acute Kidney Injury: A Retrospective Cohort Study. Issue 19 (May 2016) - Hsu, Chien-Ning; Lee, Chien-Te; Su, Chien-Hao; Wang, Yu-Ching Lily; Chen, Hsiao-Ling; Chuang, Jiin-Haur; Tain, You-Lin
Abstract : Abstract: The disease burden and outcomes of community-acquired (CA-) and hospital-acquired acute kidney injury (HA-AKI) are not well understood. The aim of the study was to investigate the incidence, outcomes, and risk factors of AKI in a large Taiwanese adult cohort. This retrospective cohort study examined 734, 340 hospital admissions from a group of hospitals within an organization in Taiwan between January 1, 2010 and December 31, 2014. Patients with AKI at discharge were classified as either CA- or HA-AKI based on the RIFLE (risk, injury, failure, loss of function, end stage of kidney disease) classification criteria. Outcomes were in-hospital mortality, dialysis, recovery of renal function, and length of stay. Risks of developing AKI were determined using multivariate logistic regression based on demographic and baseline clinical characteristics and nephrotoxin use before admission. AKI occurred in 1.68% to 2% hospital discharges among adults without and with preexisting chronic kidney disease (CKD), respectively. The incidence of CA-AKI was 17.25 and HA-AKI was 8.14 per 1000 admissions. The annual rate of CA-AKI increased from 12.43 to 19.96 per 1000 people, but the change in HA-AKI was insignificant. Comparing to CA-AKI, those with HA-AKI had higher levels of in-hospital mortality (26.07% vs 51.58%), mean length of stay (21.25 ± 22.35 vs 35.84 ± 34.62 days), and dialysis during hospitalization (1.45% vs 2.06%). Preexisting systemic diseases, including CKD were associated with increased risks of CA-AKI, and nephrotoxic polypharmacy increased risk of both CA- and HA-AKI. Patients with HA-AKI had more severe outcomes than patients with CA-AKI, and demonstrated different spectrum of risk factors. Although patients with CA-AKI with better outcomes, the incidence increased over time. It is also clear that optimal preventive and management strategies of HA- and CA-AKI are urgently needed to limit the risks in susceptible individuals. Abstract : Supplemental Digital Content is available in the text